2014
DOI: 10.1371/journal.pone.0115409
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of M. tuberculosis SerB2, an Essential HAD-Family Phosphatase, Reveals Novel Properties

Abstract: M. tuberculosis harbors an essential phosphoserine phosphatase (MtSerB2, Rv3042c) that contains two small- molecule binding ACT-domains (Pfam 01842) at the N-terminus followed by the phosphoserine phosphatase (PSP) domain. We found that exogenously added MtSerB2 elicits microtubule rearrangements in THP-1 cells. Mutational analysis demonstrates that phosphatase activity is co-related to the elicited rearrangements, while addition of the ACT-domains alone elicits no rearrangements. The enzyme is dimeric, exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(36 citation statements)
references
References 34 publications
1
35
0
Order By: Relevance
“…MtSerB2 is secreted into culture filtrate It was shown earlier by our group that exogenously added MtSerB2 elicits cytoskeletal rearrangements in the THP-1 cell line 5 . Since mycobacteria induce cytoskeleton rearrangements upon infection [12,13], the subcellular localization and the possibility of secretion of MtSerB2 into the culture filtrate was checked.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…MtSerB2 is secreted into culture filtrate It was shown earlier by our group that exogenously added MtSerB2 elicits cytoskeletal rearrangements in the THP-1 cell line 5 . Since mycobacteria induce cytoskeleton rearrangements upon infection [12,13], the subcellular localization and the possibility of secretion of MtSerB2 into the culture filtrate was checked.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, point mutants of the regulatory ACT domain such as G18A, G108A, and also those of the PSP domain such as D341/ 345N and S273A have either less or no phosphatase activity at all. Further, unlike the wild-type protein, the mutants do not exhibit functional interactions with host phosphoproteins [5]. As part of a long-term inhibitor screening program, we found that Clofazimine inhibits the phosphatase activity of MtSerB2.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, since Clorobiocin targets other mycobacterial factors also, the authors suggested a need to develop structural analogs of the identified inhibitors with MtSerB2 specific intracellular activity. Around the same time, Yadav et al [36] published another report on MtSerB2 characterization. MtSerB2 contains two small molecule binding ACT domains (Aspartate kinase, Chorismate mutase, and TyrA protein regulatory domain) at its N-terminus and a classical phosphoserine phosphatase domain (PSP) toward the C-terminal end.…”
Section: Serb2mentioning
confidence: 95%